2012
DOI: 10.1016/j.vaccine.2012.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibody dependent cell mediated cytotoxicity (ADCC) in Sm-p80-mediated protection against Schistosoma mansoni

Abstract: Schistosomiasis is a major health problem in the developing world and for international travelers to the endemic countries. Existing strategies to control schistosomiasis have had limited successes so far. The addition of an effective vaccine in existing control measures would be greatly beneficial in reducing the impact of the disease. In this regard, Sm-p80 mediated protection against intestinal schistosomiasis caused by Schistosoma mansoni has been observed to be promising in two animal models of infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
(34 reference statements)
1
24
0
1
Order By: Relevance
“…Studies utilizing schistosome non- and/or semi-permissive host such as rats have shown that resistance to schistosome infections as well as mechanism of schistosome killing are almost entirely humoral mediated by high IgG antibodies (Knopf et al 1977; Wilson et al 2008). Our group have also demonstrated the potential effector role of antibody dependent complement mediated cytotoxicity (ADCC) in schistosome killing (Torben et al 2012). In both S. japonicum challenge trials, immunizations with Sm-p80 formulated in GLA-SE elicited significant production of Sm-p80-specific antibody in immunized mice demonstrating that the vaccine formulation had a substantial impact on humoral immunity which appeared to correlate with the protection observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing schistosome non- and/or semi-permissive host such as rats have shown that resistance to schistosome infections as well as mechanism of schistosome killing are almost entirely humoral mediated by high IgG antibodies (Knopf et al 1977; Wilson et al 2008). Our group have also demonstrated the potential effector role of antibody dependent complement mediated cytotoxicity (ADCC) in schistosome killing (Torben et al 2012). In both S. japonicum challenge trials, immunizations with Sm-p80 formulated in GLA-SE elicited significant production of Sm-p80-specific antibody in immunized mice demonstrating that the vaccine formulation had a substantial impact on humoral immunity which appeared to correlate with the protection observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed an intense specific response of IgG, IgG1, IgG2a, IgM and IgE against the rFh15 antigen in immunized mice. Antibodies have been related with in vitro killing of schistosomula (Torben et al, 2012) and worm burden reduction in mice infected with S. mansoni after passive transfer of serum or purified IgG from Smp80 vaccinated baboons or mice and antibodies have been related with self cure in the rhesus macaque (Wilson and Coulson, 2009). Furthermore, we evaluated the ability of the formulation of AA0029 + Qs + rFh15 to induce protection against the cercarial challenge by S. bovis in terms of worm recovery, eggs in tissues and hepatic damage in two models BALB/c mice and golden hamster.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between Fc and FcRs can result in the death of pathogens or of cells infected with pathogens by a process known as antibody-dependent cellular cytotoxicity (156,157,158). Fc-FcR interactions are also important for phagocytosis of pathogens or of infected cells, although phagocytosis can occur in the absence of antibody or in the presence of antibody through other receptors (including complement receptors) (144).…”
Section: Antibody Functions Dependent On Fc-fc Receptor Interactionsmentioning
confidence: 99%